The mathematical description for electrochemical determination and retention of heavy metal ions by electropolymerization of Schiff base complex - Романів, Людмила Вікторівна (Applied Journal of Environmental Engineering Science, 2019)
The possibility of the heavy metal ions determination and retention (with the example of copper ion) by a new Schiff base complex electropolymerization has been studied from the theoretical point of view. It has been shown that, despite the absence of the surface instabilities, the probability of the oscillatory instability will be more expressed than in the case of the classical assisted polymer electrochemical deposition. Nevertheless, the steady-state stability is efficient, either from electroanalytical or from electrosynthetical point of view
Keywords: heavy metal ions, water purification, complex compounds, Schiff base, electropolymerization, stable steady-state